TARGET® Intracranial Aneurysm Coiling Prospective Multicenter Registry: Final Analysis of Peri-Procedural and Long-Term Safety and Efficacy Results - Zaidat, Osama O.; Castonguay, Alicia C.; Rai, Ansaar T.; Badruddin, Aamir; Mack, William J.; Alshekhlee, Amer K.; Shah, Qaisar A.; Hussain, Syed I.; Kabbani, Mouhammed R.; Bulsara, Ketan R.; Taqi, Asif M.; Janardhan, Vallabh; et al. (Frontiers in Neurology, 2019)
Background and Purpose: To describe the final results of the TARGET Registry, a multicenter, real-world study of patients with intracranial aneurysms treated with new generation TARGET Coils. Methods: The TARGET Registry is a prospective, single-arm study with independent medical event monitoring and core-lab adjudication. Patients with de novo intracranial aneurysms were embolized with either TARGET-360° or helical coils in 12 US centers. The primary outcome was aneurysm packing density (PD), which was assessed immediately post-procedure. The secondary outcomes were immediate and long-term aneurysm occlusion rate using the Raymond Scale, and independent functional outcome using the modified Rankin Scale (mRS). A secondary analysis investigated the influence of the use of 100% 360-complex coils on clinical and angiographic outcomes. Results: 148 patients with 157 aneurysms met the inclusion and exclusion criteria. 58 (39.2%) patients with ruptured and 90 (61.8%) with unruptured aneurysms were treated using TARGET 360°, helical Coils, or both. Median age was 58.3 (IQR 48.1–67.4), 73% female, and 71.6% were Caucasian. Median follow-up time was 5.9 (IQR 4.0–6.9) months. The majority were treated with TARGET 360-coils (63.7%), followed by mixed and helical coils only. Peri-procedural morbidity and mortality was seen in 2.7% of patients. A good outcome at discharge (mRS 0–2) was seen in 89.9% of the full cohort, and in 84.5 and 93.3% in the ruptured and unruptured patients, respectively. The median packing density was 28.8% (IQR 20.3–41.1). Long-term complete and near complete occlusion rate was seen in 90.4% of aneurysms and complete obliteration was seen in 66.2% of the aneurysms. No significant difference in clinical and angiographic outcomes were noted between the pure 360-complex coiling vs. mixed 360-complex/Helical coiling strategies. In a multivariate analysis, predictors for long-term aneurysm occlusion were aneurysm location, immediate occlusion grade, and aneurysm size. The long-term independent functional outcome was achieved in 128/135 (94.8%) patients and all-cause mortality was seen in 3/148 (2%) patients. Conclusion: In the multicenter TARGET Registry, two-thirds of aneurysms achieved long-term complete occlusion and 91.0% achieved complete or near complete occlusion with excellent independent functional outcome. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT01748903